A linear programming approach to test efficiency in multi-objective linear fractional programming problems - Lotfi, Farhad Hosseinzadeh; Noora, Abbas Ali; Jahanshahloo, Gholam Reza; Khodabakhshi, Mohammad; Payan, Ali (Applied mathematical modelling, 2010)
In a multi-objective linear fractional programming problem (MOLFPP), it is often useful to check the efficiency of a given feasible solution, and if the solution is efficient, it is useful to check strong or weak efficiency. In this paper, by applying a geometrical interpretation, a linear programming approach is achieved to test weak efficiency. Also, in order to test strong efficiency for a given weakly efficient point, a linear programming approach is constructed.